"Aerator Performance in Reducing Phenomenon of Cavitation in Supercritical Flow in Steep Channel Bed." - Sutopo, author 1 (2013)
Engineering International Conference "UNNES Conservation" 2013. "Establishing Collaboration Between Educational Institutions and Industrial Partness". Environmental Technology and Management Conference. No ISBN: 979-25-2783